TINGKAT PENGETAHUAN DAN RASIONALITAS SWAMEDIKASI MASYARAKAT - Betania, Putri (Journal of Pharmacy Tiara Bunda, 2021)
Self-medication has the potential to become a source of medication errors if the community's knowledge of drugs and their use is very limited. This study aims to determine the level of knowledge and rationality of self-medication community in Tanah Baru subdistrict, Beji district, Depok city. This research was conducted with a cross sectional d escriptive research method. Data were collected through filling out a validated online questionnaire. All of 375 respondents who was involved in this study were selected by the snowball sampling method. Data were analyzed using univariate and bivariate methods in the Statistical Product and Service Solution (SPSS) program version 18. The results showed that the level of knowledge in community 24% was good classified, 40.8% were medium classified and 35.2% were bad classified with an average score of 14.01. The use of self medicated drugs was 31.5% irrational and 68.5% rational. Based on the result of Chi-square and Fisher, the level of knowledge was influenced by recent education and job with p 0.00 and p 0.04 (p value <0.05). Meanwhile rationality of self medication was influenced by recent education with p 0.03 (p value <0.05). In addition, the level of knowledge about self-medication does not have a significant effect to rationality of self- medication. Recent education and job of community affect the level of self-medication knowledge, and the rationality of self-medication was affected by recent education. In addition, the level of self medication knowledge has no significant effect to the rationality of community self medication